A gestão público-privada no programa ensino médio integral em tempo integral - emiti em escolas da rede pública estadual de Santa Catarina - Guarda, Gelvane Nicole (2020)
This research, entitled “Public-private management in the Full-time High School Program - EMITI in public schools in Santa Catarina state, is part of the Educational Policies line of the Graduate Program in Education at the Federal University of Fronteira Sul - UFFS, and had a CAPES / DS scholarship. The research aimed to analyze public-private management in the Full-time High School Program - EMITI in State Education Network schools, localized in the Regional Education Coordination (CRE) - Chapecó / SC, considering the public-private partnership of Education Secretary of the State of Santa Catarina (SED) with the Ayrton Senna Institute (IAS), an outcome from the public policy of the reformulation of high school implemented by Law no. 13,415 / 2017. In this context, the following research questions emerged: (i) How does public-private relationship management take place in the Full-time High School Program - EMITI in schools of the State Education Network located in the Regional Education Coordination (CRE) - Chapecó / SC? (ii) How does the public and private trajectory and its relations with the State take place in the Brazilian context? (iii) What are the paths for the elaboration and implementation of full-time education and high school? (iv) How does public-private management appear in the Full-time High School Program - EMITI? The methodological approach has a qualitative approach, involving direct contact between the researcher and the object of study, through semi-structured interviews. For this, the research was carried out by the Ethics Committee on Research with Human Beings at UFFS. For data processing, Bardin's content analysis proposal was considered. In the present analysis, there was a progressive frequency of the private sector in the commercialization of public education. The State remains responsible for access, but the pedagogical “content” and school management is increasingly determined by institutions that introduce a neoliberal and mercantilized logic, with the justification that, in doing so, they are contributing to quality of public school training for 21st century skills.